THE INFLUENCE OF UZBEK FOLK DECORATIVE ARTS ON VISUAL ARTS AND ITS CONTEMPORARY CREATIVE INTERPRETATIONS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes Uzbek folk decorative arts and their influence on visual arts. It examines the role of decorative elements within the national art school, the harmony of patterns and colors, compositional principles, as well as rhythm and plasticity aspects. Additionally, the pedagogical significance of decorative art elements, their integration with innovative technologies in contemporary creative practices, and their role in preserving national identity are discussed. The research results can serve as a foundation for studying national heritage, creating new interpretations in visual arts, and fostering the creative development of young artists.